Implementasi Hukum Pendistribusian Bahan Bakar Minyak Bersubsidi Kepada Nelayan Kecil - Mote, Herry Hendri; Rahail, Emiliana; Rumbewas, Ricky (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
This research aims to find out how subsidized fuel oil is distributed to small fishermen by the Merauke Regency Fisheries Service based on Law Number 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Farmers and Salt Farmers. As well as knowing the procedures for obtaining distribution of subsidized fuel oil by the Merauke Regency Fisheries Service to small fishermen in Merauke Regency. This research is empirical juridical research. This research was carried out in the Merauke City Area, namely at the Arafura Buti Street Oil Fuel Station, and the Merauke Regency Fisheries Service. The results of the research in this thesis show that the regulation of the distribution of subsidized fuel oil by the Fisheries Service in distributing fuel uses a distribution strategy that is right on target by providing recommendations for purchasing subsidized fuel oil to fishermen. At the supervision stage, the government uses two control instruments, namely through recommendations given to small fishermen and supervision by assigning employees from the department to carry out supervision.